A novel quantum inspired cuckoo search for knapsack problems. (2nd September 2011) - Layeb, Abdesslem
This paper presents a new inspired algorithm called quantum inspired cuckoo search algorithm (QICSA). This one is a new framework relying on quantum computing principles and cuckoo search algorithm. The contribution consists in defining an appropriate representation scheme in the cuckoo search algorithm that allows applying successfully on combinatorial optimisation problems some quantum computing principles like qubit representation, superposition of states, measurement, and interference. This hybridisation between quantum inspired computing and bioinspired computing has led to an efficient hybrid framework which achieves better balance between exploration and exploitation capabilities of the search process. Experiments on knapsack problems show the effectiveness of the proposed framework and its ability to achieve good quality solutions.